Water in the Martian interior—The geodynamical perspective. (12th September 2016) - Breuer, Doris; Plesa, Ana‐Catalina; Tosi, Nicola; Grott, Matthias
Abstract: Petrological analysis of the Martian meteorites suggests that rheologically significant amounts of water are present in the Martian mantle. A bulk mantle water content of at least a few tens of ppm is thus expected to be present despite the potentially efficient degassing during accretion, magma ocean solidification, and subsequent volcanism. We examine the dynamical consequences of different thermochemical evolution scenarios testing whether they can lead to the formation and preservation of mantle reservoirs, and compare model predictions with available data. First, the simplest scenario of a homogenous mantle that emerges when ignoring density changes caused by the extraction of partial melt is found to be inconsistent with the isotopic evidence for distinct reservoirs provided by the analysis of the Martian meteorites. In a second scenario, reservoirs can form as a result of partial melting that induces a density change in the depleted mantle with respect to its primordial composition. However, efficient mantle mixing prevents these reservoirs from being preserved until present unless they are located in the stagnant lid. Finally, reservoirs could be formed during fractional crystallization of a magma ocean. In this case, however, the mantle would likely end up being stably stratified as a result of the global overturn expected to accompany the fractional crystallization. Depending on the assumed density contrast, little secondary crust would be produced and the lithosphere would be extremely cool and dry, in contrast to observations. In summary, it is very challenging to obtain a self‐consistent evolution scenario that satisfies all available constraints.